Asālīb al-Istimālah al-'Āṭifiyyah fī Kitāb Al-Imāmah wa al-Siyāsah: Dirāsah fī al-Binyah wa al-Dalālah - Abdul Hafidz Zaid (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2016)
The events of al-Saqīfah and the political developments surrounding them represent a significant turning point in the history of Arab political thought. Although political activities had already existed among pre-Islamic Arab tribes, the events at al-Saqīfah marked the emergence of a more organized concept of state governance. They transformed the Arab political system from a narrow tribal structure into a state-oriented political order and shifted political thinking from the pre-Islamic (Jāhiliyyah) worldview to the Islamic paradigm. This study examines the patterns and linguistic expressions of emotional persuasion employed in Arabic political discourse through Ibn Qutaybah al-Dīnawarī's Al-Imāmah wa al-Siyāsah. It aims to identify the forms of emotional persuasive expressions and analyze the contexts in which they are used from both structural and semantic perspectives.